Estudio de pre-factibilidad para la instalación de una planta productora de envases de cartón corrugado - Vargas Párraga, Flavio André (2018)
The objective of this Pre-feasibility Study is to determine the technological, economic, social and market viability for the installation of a corrugated cardboard packaging production factory that complies with the client's requirements and specifications and is friendly to the environment. This research, which will have a horizon of 10 years, has been developed in nine chapters in which it tries to describe all the methodologies that have been used to demonstrate and justify the work hypothesis and to find for the viability of the project.